Rings with nilpotent derivations of index ≤ 2 - Lukashenko, M.P. (Carpathian Mathematical Publications, 2014)
We prove that a semiprime ring with nilpotent derivations (respectively inner derivations) is differentially trivial (respectively commutative). The Jacobson radical $J(R)$ of a ring $R$ with nilpotent derivations contains all its nilpotent elements.